2018
DOI: 10.1177/1741143217751074
|View full text |Cite
|
Sign up to set email alerts
|

Primary school leadership in Malaysia: The experience of stress among deputy heads

Abstract: Unquestionably, studies focusing on school leaders’ stress while managing schools have received extensive attention. However, there is still a lack of research focusing on deputies’ stress, even though deputies play an essential role in a school’s improvement process. Despite deputies’ dual roles, it is an accepted fact that deputies do experience stress while simultaneously dealing with their ‘superiors’, fulfilling their administrative tasks and helping teachers to work at their fullest capacity. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 52 publications
(72 reference statements)
1
26
0
Order By: Relevance
“…However, previous studies on the gender difference in the stress levels of school principals have found mixed results. Although some studies have shown that male principals experienced slightly higher stress levels compared to their female counterparts [ 57 , 58 , 59 ], other studies found that females experienced higher levels of stress than males in educational settings [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies on the gender difference in the stress levels of school principals have found mixed results. Although some studies have shown that male principals experienced slightly higher stress levels compared to their female counterparts [ 57 , 58 , 59 ], other studies found that females experienced higher levels of stress than males in educational settings [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that school principals’ stress level is inversely correlated with their age [ 62 ]. Further research has suggested that the level of perceived stress varies with the experience of the school principal, as those with less experience had a higher level of perceived stress than more senior principals [ 57 ]. However, a previous study of primary and high-school teachers in Greece found that older teachers reported higher levels of stress related to the support they perceived to be receiving from the government, whereas younger teachers reported higher levels of burnout, as evidenced by emotional exhaustion and disengagement from the profession [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is, emotional help given by school principals, suggestions to do their job effectively, and encouraging approaches can be effective tools for reducing tension caused by work intensification. These important roles of school principals have been emphasized by previous studies (Searby et al, 2017;Tahir et al, 2019). On the other hand, when school principals put pressure on assistant principals instead of helping them think through their issues, assistant principals generally felt discouraged and considered quitting (Demirbilek & Bakioğlu, 2019).…”
Section: Coping Strategies For Work Intensificationmentioning
confidence: 90%
“…Research focusing on the stress of principals when managing educational institutions has received severe and widespread attention in various countries, such as Switzerland (Denecker, 2019), Malaysia (Tahir et al, 2019), Japan (Deguchi et al, 2018), Australia (Beausaert et al, 2016), United States (Grissom et al, 2016;Hancock et al, 2019;Kaufman, 2019) and Germany (Hancock et al, 2019). However, the stressful experiences of principals are still being ignored, and few have studied them Tahir et al, (2019) comprehensively, including the stress experienced by principals in Indonesia. Based on the search results for scientific works from publications about stress, Indonesian school principals are still very minimal.…”
Section: Introductionmentioning
confidence: 99%